1985
DOI: 10.2307/3899422
|View full text |Cite
|
Sign up to set email alerts
|

Response of Vegetation of the Northern Great Plains to Precipitation Amount and Grazing Intensity

Abstract: Changes in basal cover of vegetation were predicted in response to variation in precipitation and grazing intensity. Multiple regression analysis was used with basal cover as a dependent variable and precipitation parameters as independent variables to develop predictive equations. Predicted cover values were used to develop three dimensional response surfaces which describe individual species responses to fluctuating precipitation and different grazing intensities. Results indicate that each species reacts to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 6 publications
3
24
1
Order By: Relevance
“…7) are in agreement with previous findings showing that precipitation is the principal factor altering productivity of these rangelands (Whitman et al 1943;Hurt 1951;Reed and Peterson 1961;Olson et al 1985;Biondini and Manske 1996;Biondini et al 1998;. Similarly, results from this study (as well as those studies cited above) show that grazing consistently reduces herbage standing crops (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…7) are in agreement with previous findings showing that precipitation is the principal factor altering productivity of these rangelands (Whitman et al 1943;Hurt 1951;Reed and Peterson 1961;Olson et al 1985;Biondini and Manske 1996;Biondini et al 1998;. Similarly, results from this study (as well as those studies cited above) show that grazing consistently reduces herbage standing crops (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Purple sandgrass increased during the first wet period, but not the second. These temporal changes are examples of nondirectional dynamics driven by individualistic species responses to environmental variability, a phenomenon also observed by Olson et al (1985). Illius and O'Conner (1999) felt that vegetation response would be more tightly coupled to grazing intensity during periods of higher precipitation.…”
Section: (2) March 2006mentioning
confidence: 68%
“…Illius and O'Conner (1999) countered that vegetation response is coupled to grazing intensity even in ecosystems with highly variable precipitation, but the strength of the coupling is greater for more productive sites within a grazing unit and during high precipitation periods. Olson et al (1985) concluded climatic effects were dominant but that the responses of individual species to climate were mediated by stocking rate. Fuhlendorf et al (2001) found that stocking rate determined the long-range trajectory of grassland succession but that climatic fluctuations could either strengthen existing trajectories or promote alternate trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Olson et al (1985) suggested, however, that each species reacts to precipitation and grazing in a unique manner. Grazing often results in a shift in composition from tall to short species, and in selection for prostrate growth forms within a species (McNaughton 1983(McNaughton , 1984, producing a greater uniformity in the horizontal distribution of biomass than is found on nongrazed sites .…”
Section: ------------------------------------(G M 2) ----------------mentioning
confidence: 99%
“…Intensive grazing may reduce the negative effect of drought by reducing transpiring leaf area, thereby conserving soil moisture Detling 1986, Day andDetling 1994). The effects of grazing intensity on plant responses to drought are species specific (Olson et al 1985), suggesting that the interaction between drought and grazing could significantly affect botanical composition of rangelands.…”
Section: Introductionmentioning
confidence: 99%